2차원 Tent-map을 이용한 RFID 인증 프로토콜 설계 - 임거수(Geo-su Yim) (한국정보전자통신기술학회 논문지, 2020)
Recent advancements in industries and technologies have resulted in an increase in the volume of transportation, management, and distribution of logistics. Radio-frequency identification (RFID) technologies have been developed to efficiently manage such a large amount of logistics information. The use of RFID for management is being applied not only to the logistics industry, but also to the power transmission and energy management field. However, due to the limitation of program development capacity, the RFID device is limited in development, and this limitation is vulnerable to security because the existing strong encryption method cannot be used. For this reason, we designed a chaotic system for security with simple operations that are easy to apply to such a restricted environment of RFID. The designed system is a two-dimensional tent map chaotic system. In order to solve the problem of a biased distribution of signals according to the parameters of the chaotic dynamical system, the system has a cryptographic parameter( 1), a distribution parameter( 2), and a parameter( ), which is the constant point, ID value, that can be used as a key value. The designed RFID authentication system is similar to random numbers, and it has the characteristics of chaotic signals that can be reproduced with initial values. It can also solve the problem of a biased distribution of parameters, so it is deemed to be more effective than the existing encryption method using the chaotic system. 산업과 기술이 고도화되면서 물류의 운송, 관리, 유통이 대량화되었고 이런 대량의 물류 정보를 효율적으로 관리하기 위해 RFID(Radio-Frequency Identification) 기술이 개발되었다. 관리를 목적으로 하는 RFID는 물류 산업뿐만 아니라 전력전송 및 에너지관리 분야까지 산업 전반에 응용되고 있는 상태이다. 그러나 RFID 장치는 프로그램 개발 용량의 제한으로 개발에 제약을 받고 있고, 이런 제약은 기존의 강인한 암호화 방법을 사용할 수 없어서 보안에 취약함을 가지고 있다. 우리는 이런 RFID의 제약적인 환경에 적용하기 쉬운 단순 연산으로 구현할 수 있는 보안용 혼돈 시스템을 설계하였다. 설계된 시스템은 2차원 Tent-map 혼돈 시스템으로 혼돈계의 매개변수에 따른 신호의 편중 분포 문제점을 해결하기 위해 암호용 매개변수( 1)와 분포용 매개변수( 2)그리고 키값으로 사용될 수 있는 상점 ID 값을 매개변수( )로 하는 시스템이다. 설계된 RFID 인증 시스템은 난수와 유사하며 초기값으로 재생산이 가능한 혼돈 신호의 특성이 있고 매개변수에 대한 편중 분포 문제를 해결하였기 때문에 기존의 혼돈 시스템을 이용한 암호화 방법보다 효과적이라고 할 수 있다.